Effects of visual, auditory, and kinesthetic learning styles on biology achievement in a Kerinci-based religious school - Novinovrita. M; M. Eval Setiawan (JPBI (Jurnal Pendidikan Biologi Indonesia), 2025)
The Society 5.0 era demands inclusive and effective education, yet diverse student needs remain unmet due to limited personalised approaches. The visual, auditory, and kinesthetic (VAK) model offers a promising solution to improve engagement and achievement, especially in biology learning at MAN 1 Kerinci, Jambi, Indonesia. This study aimed to examine the effect of VAK (Visual, Auditory, and Kinesthetic) learning styles on students’ learning achievement in biology subjects in Madrasah Aliyah Negeri 1 Kerinci. Using a quantitative approach with a correlational design, 60 students in class VIII were selected as samples through a purposive sampling technique. Research instruments in the form of learning style questionnaires and student learning achievement data were analysed using descriptive statistics, one-way ANOVA, and Tukey’s HSD post hoc tests. The results showed that learning styles had a significant influence on student learning achievement (p < 0.05), with the auditory learning style producing the highest average achievement compared to the Visual and Kinesthetic learning styles. These findings support the importance of customising learning strategies based on students' learning styles to improve learning outcomes. Recommendations from this study emphasise the need for varied, adaptive, and inclusive learning approaches to optimise students' academic potential.